Biodegradation of oil refinery residues using mixed-culture of microorganisms isolated from a landfarming - Morais, Eduardo Beraldo de [UNESP]; Tauk-Tornisielo, Sâmia Maria [UNESP] (Brazilian Archives of Biology and Technology, 2009)
Neste estudo foi investigado o potencial de um inóculo composto de cultura mista de bactérias e fungos, isolados do landfarming da Refinaria de Paulínia, Brasil, em degradar resíduos oleosos gerados no processo de refinamento de petróleo. O isolamento desses microrganismos foi realizado previamente, supondo-se que estejam melhor adaptados aos hidrocarbonetos de petróleo uma vez que o landfarming consiste em área impactada por deposição de tais compostos. Utilizou-se o teste respirométrico de Bartha e Pramer no intuito de verificar a taxa de biodegradação dos hidrocarbonetos pela cultura mista de microrganismos através da evolução de CO2. Os resultados obtidos para a eficiência da biodegradação não apresentaram diferença estatisticamente significativa (P>0.05) indicando que não houve aumento do processo de biodegradação com o uso do inóculo. A adição de nutrientes (N, P, K) tampouco contribuiu para aumentar a biodegradação do resíduo oleoso estudado.

In this study, the potential for using an inoculum composed of a mixed-culture of bacteria and fungi, isolated from a landfarming at the Paulínia Oil Refinery, Brazil, to degrade oil residues generated in the process of petroleum refinement was investigated. The isolation of these microorganisms was carried out beforehand, assuming that they would be better adapted to petroleum hydrocarbons, as the landfarming consisted of an area impacted by the deposit of such compounds. The Bartha and Pramer respirometric test was used to measure the rate of biodegradation of the hydrocarbons by the mixed-culture of microorganisms via the evolution of CO2. The results obtained with respect to the efficiency of biodegradation showed no significant differences (P>0.05), indicating no increase in the biodegradation process using the inoculum. The addition of nutrients (N, P, K) also did not contribute to an increase in biodegradation of the oil residue studied.
Keywords: biodegradation; oil residue; petroleum; inoculum; mixed-culture